Metal/Ca ratios in pockmarks and adjacent sediments on the SW Atlantic slope: Implications for redox potential and modern seepage - dos Santos, Rosangela Felício; Nagaoka, Doris; Ramos, Raissa Basti; Salaroli, Alexandre Barbosa; Taniguchi, Satie; Figueira, Rubens Cesar Lopes; Bícego, Marcia Caruso; Lobo, Francisco José; Schattner, Uri; de Mahiques, Michel Michaelovitch (Journal of geochemical exploration, 2018)
Metal/Ca ratios and their corresponding enrichment factors (EFs) in bulk sediment samples collected at a mixed carbonate-siliciclastic continental slope setting with an extensive pockmark field were measured and analyzed to find evidence of lateral differences in the redox potential and recent seepage activity inside the pockmarks. The analyzed ratios point to metal enrichments that indicate variations in the redox potential inside the pockmarks compared to the adjacent areas, as shown by the Cu/Ca, Ni/Ca and Zn/Ca EFs. Slight but statistically significant differences in the Mg/Ca ratios indicated that the formation of Mg-enriched carbonates within the pockmarks is presently taking place, attesting the maintenance of seepage in the shallow sedimentary column. Recent seepage activity was also confirmed by the upward enrichment of Ba in the sedimentary column. Our study provides direct evidence for pockmark activity and reinforces the need for an extended analysis of the geochemistry of natural seepages on the SW Atlantic margin, an area that has still not been studied in relation to this subject. [Display omitted] •We recognized distinct patterns of Metal/Ca rations inside pockmarks and in the adjacent areas.•The Mg/Ca – Sr/Ca end-member model was successfully applied in our data.•There are evidences of modern seepage associated with pockmarks.